A randomized, placebo-controlled trial of late Na current inhibition (ranolazine) in coronary microvascular dysfunction (CMD): impact on angina and myocardial perfusion reserve. (27th November 2015) - Bairey Merz, C. Noel; Handberg, Eileen M.; Shufelt, Chrisandra L.; Mehta, Puja K.; Minissian, Margo B.; Wei, Janet; Thomson, Louise E.J.; Berman, Daniel S.; Shaw, Leslee J.; Petersen, John W.; Brown, Garrett H.; Anderson, R. David; et al.
Abstract : Aims: The mechanistic basis of the symptoms and signs of myocardial ischaemia in patients without obstructive coronary artery disease (CAD) and evidence of coronary microvascular dysfunction (CMD) is unclear. The aim of this study was to mechanistically test short-term late sodium current inhibition (ranolazine) in such subjects on angina, myocardial perfusion reserve index, and diastolic filling. Materials and results: Randomized, double-blind, placebo-controlled, crossover, mechanistic trial in subjects with evidence of CMD [invasive coronary reactivity testing or non-invasive cardiac magnetic resonance imaging myocardial perfusion reserve index (MPRI)]. Short-term oral ranolazine 500–1000 mg twice daily for 2 weeks vs. placebo. Angina measured by Seattle Angina Questionnaire (SAQ) and SAQ-7 (co-primaries), diary angina (secondary), stress MPRI, diastolic filling, quality of life (QoL). Of 128 (96% women) subjects, no treatment differences in the outcomes were observed. Peak heart rate was lower during pharmacological stress during ranolazine (−3.55 b.p.m., P < 0.001). The change in SAQ-7 directly correlated with the change in MPRI (correlation 0.25, P = 0.005). The change in MPRI predicted the change in SAQ QoL, adjusted for body mass index (BMI), prior myocardial infarction, and site ( P = 0.0032). Low coronary flow reserve (CFR <2.5) subjects improved MPRI ( P < 0.0137), SAQ angina frequency ( P = 0.027), and SAQ-7 ( P = 0.041). Conclusions: In this mechanistic trial among symptomatic subjects, no obstructive CAD, short-term late sodium current inhibition was not generally effective for SAQ angina. Angina and myocardial perfusion reserve changes were related, supporting the notion that strategies to improve ischaemia should be tested in these subjects. Trial registration: clinicaltrials.gov Identifier: NCT01342029.